TEST OF THE INHIBITOR EFFECTIVENESS OF THE COMBINATION OF ETHANOL EXTRACT OF LEMON LEAVES (Cymbopogon citratus) AND GREEN BETEL LEAF (Piper betle L.) AGAINST Staphylococcus aureus BACTERIA - Octora, Debi Dinha; Samuel Marpaung; Jhoti Sumitra (Jurnal FARMASIMED (JFM), 2023)
The discovery of natural substances has the potential for applications in the development of pharmaceuticals or natural alternatives to combat bacterial infections. Green betel leaves (Piper betle L.) and lemongrass stems (Cymbopogon citratus) may aid in treating infections due to their specific strength in bacteria eradication. Staphylococcus aureus is one of the pathogenic bacteria types that can cause serious infections and skin disorders under conducive conditions, such as acne and boils. The aim of this study is to determine the antibacterial activity using the maceration and disk diffusion methods on lemongrass stem and green betel leaf extracts against Staphylococcus aureus bacteria. The research conducted is qualitative in nature and aims to assess the inhibitory effect of the combination of ethanol extracts from lemongrass and green betel leaves at various concentrations on the growth of Staphylococcus aureus bacteria. Different concentrations of green betel leaf and lemongrass stem extracts were also tested to determine the most effective concentration in inhibiting bacterial growth. The results demonstrate that specific concentrations of green betel leaf and lemongrass stem extracts have a stronger antibacterial effect compared to other concentrations. The combination of ethanol extracts from lemongrass stems and green betel leaves can inhibit the growth of Staphylococcus aureus bacteria using the paper disk method, with inhibition zone diameters observed for each extract concentration and the positive control Ciprofloxacin, which had a diameter of 25.92 mm. The best concentration formula for the combination of lemongrass stem (Cymbopogon citratus) and green betel leaf (Piper betle L.) ethanol extracts is at 15% concentration, resulting in an average diameter of 18.90 mm. Keywords: Antibacterial, Piper betle L., Cymbopogon citratus, Staphylococcus aureus